Face Processing in Infancy and Beyond The Case of Social Categories. [article]. - Quinn, Paul C.
Prior reviews of infant face processing have emphasized how infants respond to faces in general. This review highlights how infants come to respond differentially to social categories of faces based on differential experience, with a focus on race and gender. We examine six different behaviors: preference, recognition, scanning, category formation, association with emotion, and selective learning. Although some aspects of infant responding to face race and gender may be accounted for by traditional models of perceptual development, other aspects suggest the need for a broader model that links perceptual development with social and emotional development. We also consider how responding to face race and gender in infancy may presage responding to these categories beyond infancy and discuss how social biases favoring own-race and female faces are formed. -- (from the author)